Elite Alleles of EPE1 Identified via Genome-wide Association Studies Increase Panicle Elongation Length in Rice - Hao Sun; Qiqi Yao; Mei Hai; Tianhu Li; Jinghan Sun; Zhengbo Liu; Yang Ang; Yingying Zhao; Yanan Zhang; Xianping Cheng; Tao Huang; Yinping Chang; et al. (Rice)
Abstract Panicle elongation length (PEL), which determines panicle exsertion, is an important outcrossing-related trait. Mining genes controlling PEL in rice (Oryza sativa L.) has great practical significance in breeding cytoplasmic male sterility (CMS) lines with increased PEL and simplified, high-efficiency seed production. Genome-wide association studies (GWAS) were performed on the PELs of 440 rice accessions in 2022 and 2023, considering 3.17 million single-nucleotide polymorphisms (SNPs) to detect the effects of different genes on PEL. A total of five quantitative trait loci (QTLs) significantly associated with PEL were detected in both years by using the general linear model (GLM) and the mixed linear model (MLM). Notably, our study identified a previously unreported QTL, qPE2.1. Three candidate genes associated with PEL were predicted by non-synonymous SNPs and functional annotation. We characterize one gibberellin (GA)-related gene, LOC_Os02g41954 (OsGA2ox9), which encodes gibberellin 2-beta-dioxygenase 7 located in the cell membrane and nucleus. Gibberellin 2-oxidase (GA2ox) has been reported to control GA levels by inactivating GA via 2-β hydroxylation. Compared with the short PELs of wild plants, mutant plants with Cas9-induced knockout (KO) of OsGA2ox9 exhibit long PELs. Therefore, OsGA2ox9 was identified as the key gene controlling PEL in rice. Haplotype analysis showed that the two polymorphisms of HapD cause amino acid residue changes from phenylalanine to leucine (F/L43) and isoleucine to phenylalanine (I/F52), which lead to the enhancement of panicle exsertion; therefore, we renamed this gene ENHANCED PANICLE EXSERTION (EPE1). Our study showed that EPE1 (OsGA2ox9) negatively regulated GA4 content in rice. Elite alleles of EPE1 can be used to further improve PEL in CMS lines to increase the outcrossing rate and yield or seed production in hybrid rice breeding.